Synchronous reference frame DQ current control for single phase grid connected cascaded H bridge multilevel inverter - S. Kirthika Devi, V; G. Srivani, S (International Journal of Engineering and Technology, 2018)
The main focus on this paper deals with a current control technique for the inverter using a PV system for grid connected topology. The work of this paper is to evolve the PV model by tracking maximum power point using Incremental conductance algorithm by applying synchronous reference frame control method for single phase transformer less cascaded H Bridge Multilevel Inverter via boost converter system connected to 230V grid. A Phase shifted pulse width modulation technique is also projected in order to afford the pulse for voltage source inverter. The mathematical expressions for the control design for the single phase system is expressed in this paper. The analysis of the control is adopted using PI control method and is executed in synchronous rotating d-q reference frame in order to carry out the response of the best output voltage for the grid connected single phase PV system. The d-q technique is applicable only for the three phase system due to the minimum requirement of two independent phases. Hence one quadrature phase inverter is added additionally in the control method. The simulation is done using MATLAB/SIMULINK.